Perspektif Buddhis Tentang Makanan: Memahami Konsep Halal Dan Haram - Medhacitto, Tri Saputra; Sukodoyo; Suranto (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya Wonogiri, 2025)
The research examines the Buddhist perspective on food consumption, by exploring the understanding of the concepts of halal and haram in Buddhism. This research was conducted using a literature study approach, by examining Buddhist scriptures and relevant literature such as books, journals, scientific articles, to compare the Buddhist perspective on eating etiquette with the concepts of halal and haram in Islam. The findings show that halal and haram refer to foods that are and are not allowed to be consumed. Although Buddhism does not have specific terms similar to halal and haram, Buddhism has a set of moral and ethical principles that have the same function as the concepts of halal and haram, which guide humanity to determine what is permissible and what is not. Buddhism has the term